Barrelman Radio Program - Barrelman (Radio program); Weir, Gail, 1948- (1937)
This collection contains the papers of The Barrelman radio program, the scripts of which were generated by Joseph R. Smallwood and Michael F. Harrington, the two announcers who served as the Barrelman in St. John's. The St. John's scripts were recycled for the Corner Brook series, which was entitled O'Leary Newfoundland Program and hosted by Stan O'Leary, brother of the program's sponsor, F.M. O'Leary. These vary somewhat from the St. John's scripts and are also included in the collection. This collection will be of interest to historians and biographers researching Smallwood's and Harrington's early careers; those studying the lives of other prominent Newfoundlanders, especially those who made a name for themselves outside Newfoundland; folklorists, who will find a wealth of material on a wide range of folkloristic genres; those interested in early radio programming in Newfoundland, as well as diversions of the time; students of vernacular literature; and anyone seeking a sampling of Newfoundland's history, culture and social life.